Risk of supply insecurity with weather condition-based operation of plug in hybrid electric vehicles - Jayaweera, Dilan; Islam, Syed (The Institution of Engineering and Technology, 2014)
Plug in hybrid electric vehicles (PHEVs) can be a strategic source to mitigate risk of supply insecurity in an active distribution network. This study proposes a new methodology to quantify the risk of supply insecurity with weather condition based operation of PHEVs in an active distribution network. The approach divides operating characteristics of PHEVs into charging, discharging and null. Operation of PHEVs with change in weather conditions, intermittent characteristics of distributed generation, sector customer demand characteristics and random outages of components are modelled on Markovchain Monte Carlo simulation. A set of case studies are performed considering distributed operation of PHEVs as oppose to central operation of conventional units. Results suggest that distributed operation of PHEVs can potentially mitigate risk of supply insecurity of moderately stressed networks. Highly stressed networks, which are operated with PHEVs, need supplementary supports from conventional units to mitigate risk of supply insecurity.